KARAKTERISTIK BIODIESEL BIJI BINTARO (Cerbera manghas L) DENGAN PROSES MODIFIKASI - Djeni Hendra; Santiyo Wibowo; Novitri Hastuti; Heru S.Wibisono (BRIN Publishing, 2016)
Biodiesel is a diesel fuel made from vegetable oils extracted from various forest plants. This paper studies the characteristics of biodiesel made from Bintaro's seed (Cerbera manghas L.) by modified process. The modification process includes pretreatment and degumming processes. In the pretreatment process, modification includes raw material's treatment such as steaming, washing, drying and compressing. Degumming modification process includes addition of phosphoric acid catalyst, then bentonite; esterification by methanol acid catalyst and followed by addition of zeolite; the transesterification process by methanol bases catalyst. Results show that physico-chemical properties of biodiesel made from Bintaro's seeds including acid value, density, iod number, viscosity and ester-alkyl content met to Indonesian National Standard (SNI) on Biodiesel.